2005
DOI: 10.1128/cdli.12.9.1085-1093.2005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Inflammatory Mediators during Start of Fever in Differential Diagnosis of Gram-Negative and Gram-Positive Infections in Leukopenic Rats

Abstract: Gram-negative and gram-positive infections have been considered the most important causes of morbidity and mortality in patients with leukopenia following chemotherapy. However, discrimination between bacterial infections and harmless fever episodes is difficult. Because classical inflammatory signs of infection are often absent and fever is frequently the only sign of infection, the aim of this study was to assess the significance of serum interleukin-6 (IL-6), IL-10, macrophage inflammatory protein-2 (MIP-2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 43 publications
(81 reference statements)
4
39
0
Order By: Relevance
“…In bacterial sepsis, the innate immune system provides both the initial immune responses and the early inflammatory responses (1,8,12). Early responses to infections with Grϩ and GrϪ bacteria have been shown in previous studies to involve different cytokine profiles (9,16,25,51,54). Other studies have found that infections with GrϪ bacteria activate Toll-like receptor 4 (TLR4) primarily with lipopolysaccharide (LPS), a membrane component of GrϪ bacteria (26,27,44,53).…”
mentioning
confidence: 99%
“…In bacterial sepsis, the innate immune system provides both the initial immune responses and the early inflammatory responses (1,8,12). Early responses to infections with Grϩ and GrϪ bacteria have been shown in previous studies to involve different cytokine profiles (9,16,25,51,54). Other studies have found that infections with GrϪ bacteria activate Toll-like receptor 4 (TLR4) primarily with lipopolysaccharide (LPS), a membrane component of GrϪ bacteria (26,27,44,53).…”
mentioning
confidence: 99%
“…For example, the peptidoglycan by product muramyl dipeptide (MDP) is a key element in the immune response to Grampositive bacteria which lack LPS (Tavares et al, 2005). In contrast to LPS, the response to MDP is CD14-independent, and is recognized by nucleotide-binding oligomerization domain 2 (NOD2) but not "Toll-like" receptors such as LPS (Girardin et al, 2003).…”
mentioning
confidence: 99%
“…The PCT elevation could be, at least in part, related to the characteristics of the pathogen in the systemic bacterial infection. It has been shown in vitro that PCT value was significantly higher in the supernatants of cultured human cells stimulated with LPS than in those stimulated with muramyl dipeptide, a component of the outer membrane of the GP bacteria [12]. In a study, the positive value of PCT in the bacterial infection rate was much higher than that of CRP and WBC, and the difference had a statistical significance (p<0.05).…”
Section: Discussionmentioning
confidence: 92%